Adrenocortical responsiveness to infusions of physiological doses of ACTH is not altered in posttraumatic stress disorder - Radant, Allen D.; Dobie, Dorcas J.; Peskind, Elaine R.; Murburg, M. Michele; Petrie, Eric C.; Kanter, Evan D.; Raskind, Murray A.; Wilkinson, Charles W. (Frontiers in Behavioral Neuroscience, 2009)
Early studies of posttraumatic stress disorder (PTSD) reported that abnormal function of the hypothalamic-pituitary-adrenocortical (HPA) system was associated with the disorder. However, subsequent studies attempting to identify a specific aspect of HPA dysfunction that characterizes PTSD have been marked by considerable inconsistency of results. A facet of HPA regulation that has been considered but not definitively investigated is the possibility that the responsiveness of the adrenal cortex to physiological concentrations of ACTH is diminished in PTSD. Relationships between PTSD and the adrenal androgen dehydroepiandrosterone (DHEA) have also been postulated. In this study we investigated the magnitude and time course of changes in concentrations of plasma cortisol and DHEA in response to bolus infusions of physiological doses of ACTH 1-24 in PTSD patients and control subjects. We found no evidence for PTSD-related alterations in cortisol or DHEA secretion in response to stimulation by low doses of ACTH and conclude that adrenocortical responsiveness is normal in PTSD. Results from this and other studies suggest that the occurrence of defects in HPA function in PTSD may be specific responses to particular combinations of trauma type, genetic susceptibility, and individual history.